2016
DOI: 10.1016/j.jcis.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

A GCMC simulation and experimental study of krypton adsorption/desorption hysteresis on a graphite surface

Abstract: Adsorption isotherms and isosteric heats of krypton on a highly graphitized carbon black, Carbopack F, have been studied with a combination of Monte Carlo simulation and high-resolution experiments at 77K and 87K. Our investigation sheds light on the microscopic origin of the experimentally observed, horizontal hysteresis loop in the first layer, and the vertical hysteresis-loop in the second layer, and is found to be in agreement with our recent Monte Carlo simulation study (Diao et al., 2015). From detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Computer simulation studies of adsorption of gases on graphite using the homogeneous continuum 10-4-3 model 1 have been used to investigate the mechanism of adsorption for a number of single and multisite molecules, for example, argon, 2-4 methane, 5 krypton, 6,7 nitrogen, 8,9 carbon dioxide, 10 benzene, 11 ethane, 12 ethylene, 12 propylene, 13 carbon tetrachloride, 14 n-butane, n-pentane, n-hexane, 15 methanol, 16,17 ethanol, 17 and ammonia. 18 This model assumes that graphite is a uniformly homogeneous continuum solid, and its derivation implies the following assumptions: (1) the solid is built from stacked, equally spaced graphene layers, (2) there is an infinite number of layers, and (3) the carbon atom molecular parameters are invariant for all layers (collision diameter a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation studies of adsorption of gases on graphite using the homogeneous continuum 10-4-3 model 1 have been used to investigate the mechanism of adsorption for a number of single and multisite molecules, for example, argon, 2-4 methane, 5 krypton, 6,7 nitrogen, 8,9 carbon dioxide, 10 benzene, 11 ethane, 12 ethylene, 12 propylene, 13 carbon tetrachloride, 14 n-butane, n-pentane, n-hexane, 15 methanol, 16,17 ethanol, 17 and ammonia. 18 This model assumes that graphite is a uniformly homogeneous continuum solid, and its derivation implies the following assumptions: (1) the solid is built from stacked, equally spaced graphene layers, (2) there is an infinite number of layers, and (3) the carbon atom molecular parameters are invariant for all layers (collision diameter a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the adsorption of Ar/Mg (D*=3.5) 92 shows non-wetting and pre-wetting transitions for temperature above the bulk triple point of Ar whereas Ar/Graphite (D*=9) always shows continuous wetting for the same temperature range 43,49,109 . This contrast of behaviour is also observed for the adsorption of other simple gases on alkali metals 86,92,93,97,98,102 and graphite 26,28,44,110 . Macroscopically, the wetting/non-wetting is determined from the contact angle between the liquid film and solid substrate at the saturation vapour pressure P0 88 .…”
Section: Adsorption Of Polar Gases On Gtcbsupporting
confidence: 53%
“…Experimental studies of non-associating fluids (e.g. Xe [21][22][23][24] , Ne [25][26][27] , Kr 22,[28][29][30] , Ar [31][32][33] , N2 [33][34][35] , the oxides of carbon 36,37 and hydrocarbons, including CH4 38,39 , C2H4 40,41 and benzene 42 ) have revealed that these simple fluids do not interact specifically with functional groups and typically will adsorb on the basal plane with a molecular layering process 21,38,[43][44][45][46][47][48][49] due to the dominance of the fluid-basal plane interaction [50][51][52][53][54][55] over the fluid-fluid interaction. The characteristic features of adsorption on homogeneous surface include: (1) existence of a well-defined Henry constant as manifested by a slope of unity in the plot of logarithm of the amount adsorbed versus the logarithm of pressure over the low pressure region 56 .…”
Section: Adsorption Of Non-polar Gases On Gtcbmentioning
confidence: 99%
“…There is an initial decrease in the SF contribution, a trend that is not commonly observed for simple gases (i.e. Ar [30], Kr [31]),…”
Section: Decomposition Of Isosteric Heat Profilementioning
confidence: 78%